KOMUNIKASI ANTAR PERSONA ANTARA PERAWAT DAN KELUARGA PASIEN DI RUMAH SAKIT UMUM DAERAH KABUPATEN MUNA - La Tarifu (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2016)
This study aims to know the communication of interpersonal relations between nurse and patient’s family in Regional Hospital of Muna Regency. Theoretically, the advantage of this study is this study will enrich researches which discusses about communication problems in the case of interpersonal relation as well as an interesting study in the science of communication, especially interpersonal communication. Theory which is used in this study called interpersonal communication theory by Joseph D. Vito. The data obtained from this research are analyzed by using Qualitative Descriptive Technique. The results of this study indicate that interpersonal communication between the nurse and patient's family has not been fully implemented properly because of the problem of the number of jobs and the number of patients. A nurse demands a professional in having a large number of patients to serve as being one of the factors of why nurses are also required for professionals and provide excellent service.